2009
DOI: 10.1007/bf03326086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spatial and seasonal variations in surface water quality using multivariate statistical techniques

Abstract: ABSTRACT:In this study, spatial and seasonal variations of water quality in Haraz River Basin were evaluated using multivariate statistical techniques, such as cluster analysis, principal component analysis and factor analysis. Water quality data collected from 8 sampling stations in river during 4 seasons (Summer and Autumn of 2007, Winter and Spring of 2008) were analyzed for 10 parameters (dissolved oxygen, Fecal Coliform, pH, water temperature, biochemical oxygen demand, nitrate, total phosphate, turbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(119 citation statements)
references
References 36 publications
4
101
0
2
Order By: Relevance
“…The CA enabled us to categorize sampling locations based on water quality, so that in future studies, the number of sampling locations can be minimized for cost-effective monitoring of water quality in Tiaoxi River by choosing a few locations from each cluster based on the distance distribution and pollution levels in those locations. Previous studies have reported that a similar strategy has been successfully applied in water quality monitoring programs elsewhere [12,13,61,62], and the Tiaoxi River Taihu catchment is therefore similarly amenable to this rational approach. the number of sampling locations can be minimized for cost-effective monitoring of water quality in Tiaoxi River by choosing a few locations from each cluster based on the distance distribution and pollution levels in those locations.…”
Section: Cluster Analysis For Spatial Groupingmentioning
confidence: 99%
“…The CA enabled us to categorize sampling locations based on water quality, so that in future studies, the number of sampling locations can be minimized for cost-effective monitoring of water quality in Tiaoxi River by choosing a few locations from each cluster based on the distance distribution and pollution levels in those locations. Previous studies have reported that a similar strategy has been successfully applied in water quality monitoring programs elsewhere [12,13,61,62], and the Tiaoxi River Taihu catchment is therefore similarly amenable to this rational approach. the number of sampling locations can be minimized for cost-effective monitoring of water quality in Tiaoxi River by choosing a few locations from each cluster based on the distance distribution and pollution levels in those locations.…”
Section: Cluster Analysis For Spatial Groupingmentioning
confidence: 99%
“…When the eigenvalue of a principal component is equal to, or greater than, 1, the result of the principal component analysis is considered significant [24], [25]. To minimize the variations among the variables for each factor, the factor axes were varimax-rotated.…”
Section: E Principal Component Analysis (Pca)mentioning
confidence: 99%
“…Portmann et al (2009) studied the spatial and seasonal patterns for climate change, temperatures and precipitations. Nobre et al (2011) introduce an spatially varying Autoregressive Processes for satellite data on sea surface temperature for the North Pacific to illustrate how the model can be used to separate trends, cycles, and short-term variability for high-frequency environmental data; a multivariate GSTAR has been developed by Pejman et al (2009) for the study of the water quality.…”
Section: Introductionmentioning
confidence: 99%